The never-ending enigma of immune thrombocytopenia - Hoffmeister, Karin M. (Blood, 2020)
In this issue of Blood, Morodomi et al advance our understanding of the mechanisms involved in antibody-mediated immune thrombocytopenia (ITP).(1)